1984
DOI: 10.1210/jcem-58-5-857
|View full text |Cite
|
Sign up to set email alerts
|

True Precocious Puberty Complicating Congenital Adrenal Hyperplasia: Treatment with a Luteinizing Hormone-Releasing Hormone Analog*

Abstract: Congenital adrenal hyperplasia (CAH) is a recognized cause of precocious pseudopuberty. Some children with CAH also develop true precocious puberty with early maturation of the hypothalamic-pituitary-gonadal axis. We have seen four such children (three boys and one girl) who had the diagnosis of CAH made between the ages of 3 and 6 yr. These patients were treated with standard doses of hydrocortisone and fludrocortisone. A diagnosis of true precocious puberty was made because of testicular enlargement in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
8

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 22 publications
0
65
1
8
Order By: Relevance
“…True CPP has been described previously in classical 21-OHD (29), NC21-OHD (22), and virilizing adrenal tumors (30), either at presentation or following institution of therapy when the hyperandrogenism resolved. The presentation of CPP associated with hyperandrogenism usually correlates with advanced BA to the range of the pubertal years (29,30). Our group B patients did tend to have more advanced BA SDS at diagnosis than group A (Table 2), but only three out of six had a BA of > 8 years at gonadarche, which appeared before initiation of therapy, i.e.…”
Section: Discussionmentioning
confidence: 60%
“…True CPP has been described previously in classical 21-OHD (29), NC21-OHD (22), and virilizing adrenal tumors (30), either at presentation or following institution of therapy when the hyperandrogenism resolved. The presentation of CPP associated with hyperandrogenism usually correlates with advanced BA to the range of the pubertal years (29,30). Our group B patients did tend to have more advanced BA SDS at diagnosis than group A (Table 2), but only three out of six had a BA of > 8 years at gonadarche, which appeared before initiation of therapy, i.e.…”
Section: Discussionmentioning
confidence: 60%
“…The condition is rare and most of the identified cases in boys are due to simple virilising and non-classic CAH variants. In CAH, transition from precocious pseudo-puberty to secondary central precocious puberty has been observed and is thought to be due to the induction of the GNRH pulse generator by persistently increased sex steroids (66). Pubertal progression in central precocious puberty is efficiently halted by GNRH analogues blocking GNRH action (67,68).…”
Section: Pa: Definitions and Differential Diagnosismentioning
confidence: 99%
“…. Several small studies have demonstrated a significant improvement in adult height in children with CAH and secondary CPP who were treated with a GnRHa (37)(38)(39)(40). However, none have been randomized prospective trials, which likely explains why routine use of GnRHas to treat secondary CPP in children with CAH is not recommended by consensus guidelines (41).…”
Section: Gnrhas In Congenital Adrenal Hyperplasiamentioning
confidence: 99%